2021
DOI: 10.3390/jcm10153448
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the SARC-F Questionnaire for Sarcopenia Screening in Patients with Chronic Liver Disease: A Multicenter Cross-Sectional Study in Japan

Abstract: Diagnosing sarcopenia is challenging. This multicenter cross-sectional study aimed to evaluate the utility of the SARC-F score system for identifying sarcopenia in patients with chronic liver disease (CLD). We enrolled 717 patients from five participating centers who completed the SARC-F between November 2019 and March 2021. Sarcopenia was diagnosed based on the Japan Society of Hepatology Working Group on Sarcopenia in Liver Disease Consensus. Muscle strength was estimated using a grip dynamometer, and muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…As described above, a relatively lower sensitivity of the SARC-F score for sarcopenia may be a problem, which is identical to our data [ 21 , 22 , 23 ]. Hanai et al reported in their large cohort with chronic liver disease that a SARC-F score = 1 demonstrated a stronger discrimination capability for selecting sarcopenia than a SARC-F score = 4, with an AUC of 0.68, and with the sensitivity/specificity of 0.65/0.68 [ 36 ]. In view of these, the cutoff point of the SARC-F score should be carefully reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…As described above, a relatively lower sensitivity of the SARC-F score for sarcopenia may be a problem, which is identical to our data [ 21 , 22 , 23 ]. Hanai et al reported in their large cohort with chronic liver disease that a SARC-F score = 1 demonstrated a stronger discrimination capability for selecting sarcopenia than a SARC-F score = 4, with an AUC of 0.68, and with the sensitivity/specificity of 0.65/0.68 [ 36 ]. In view of these, the cutoff point of the SARC-F score should be carefully reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 127 patients undergoing peritoneal dialysis, the sensitivity and specificity of SARC-F for sarcopenia assessed by AWGS2 were 0.700 and 0.812, respectively (48). In a study of 717 patients with chronic liver diseases (CLDs), the sensitivity and specificity of SARC-F for sarcopenia assessed by the JSH were 0.65 and 0.68 when the cutoff value of SARC-F was set at 1, and the predictive ability was better than when the cutoff value of SARC-F was set at 4 (49). In a study of 94 patients with systemic sclerosis, the sensitivity and specificity for sarcopenia assessed by EWGSOP2 were 0.400 and 0.810 for the SARC-F, and 0.533 and 0.848 for the SARCcalf, respectively (50).…”
Section: Clinical Significance Of the Sarc-f According To Diseasesmentioning
confidence: 99%
“…All individuals with SARC‐values ≥4 were counted as sarcopenic. 5 , 6 Additionally, all individuals underwent a handgrip strength test. Here, values ≤18 kg for women or 25.5 kg for men were counted as sarcopenic.…”
Section: Methodsmentioning
confidence: 99%
“…Sarcopenia was assessed in all patients and controls using the SARC‐F questionnaire (Strength, Assistance in walking, Rise from a chair, Climb stairs, Falls). All individuals with SARC‐values ≥4 were counted as sarcopenic 5,6 . Additionally, all individuals underwent a handgrip strength test.…”
Section: Methodsmentioning
confidence: 99%